2022
DOI: 10.1186/s12889-021-12479-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between COVID-19 vaccine hesitancy and generalized trust, depression, generalized anxiety, and fear of COVID-19

Abstract: Background Although numerous studies have been published on the predictors of COVID-19 vaccine hesitancy, some possible predictors remain underexplored. In this study, we explored the associations of unwillingness and indecisiveness regarding COVID-19 vaccination with generalized trust, mental health conditions such as depression and generalized anxiety, and fear of COVID-19. Methods Data of wave 1 (from October 27 till November 6, 2020) and wave 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 76 publications
(125 reference statements)
8
74
2
1
Order By: Relevance
“… 32 , 33 High general anxiety was correlated with the unwillingness to receive the vaccine. 34 Although only a few respondents had COVID-19 vaccination-related anxiety in the current study, vaccination-related anxiety was the factor associated most significantly with vaccine hesitancy in this study. Anxieties could be influenced by several factors.…”
Section: Discussioncontrasting
confidence: 50%
“… 32 , 33 High general anxiety was correlated with the unwillingness to receive the vaccine. 34 Although only a few respondents had COVID-19 vaccination-related anxiety in the current study, vaccination-related anxiety was the factor associated most significantly with vaccine hesitancy in this study. Anxieties could be influenced by several factors.…”
Section: Discussioncontrasting
confidence: 50%
“…Those with higher VL may have the ability to source information and decide to not select mRNA, instead choosing previously demonstrated vaccine types such as adenovirus-based. Both VF and VH were associated with acceptance or willingness to receive the vaccination [47][48][49][50], while broadly based studies revealed that fear of the disease encouraged vaccination [48,51,52]. Our team also investigated the impact of VF and VH on AV.…”
Section: Plos Onementioning
confidence: 99%
“…Earlier studies assessing vaccine hesitancy have demonstrated that poor mental health is associated with higher vaccine acceptance toward influenza vaccines ( 34 , 35 ). In studies conducted assessing the relation of mental health with COVID-19 vaccine hesitancy there were conflicting results across countries ( 36 38 ). At the time of the manuscript preparation (18th April, 2022), to our knowledge there were no studies that evaluated the impact of mental health on vaccine hesitancy in India and Saudi Arabia population.…”
Section: Introductionmentioning
confidence: 99%